Exploring associations between adverse childhood experiences and oral health among children and adolescents. (28th August 2019) - Crouch, Elizabeth; Nelson, Joni; Radcliff, Elizabeth; Martin, Amy
Abstract: Objectives: The aim of this article is to examine the association between preventive dental care and adverse childhood experiences (ACEs), and the association between tooth decay and ACEs, controlling for preventive dental care. Methods: A cross‐sectional study was conducted with a sample of 33, 395 respondents from the 2016 National Survey of Children's Health, a nationally representative sample of US children. Sociodemographic information, ACE questions, and oral health and health‐care utilization information were used. Descriptive statistics, bivariate analyses, and multivariable regression models were performed. Results: Children with four or more ACEs were less likely to have a preventive dental visit than children with less than four ACEs (79.7 percent versus 88.7 percent, P < 0.0001). Children with four or more ACEs were more likely to have tooth decay (26.7 percent versus 12.5 percent, P < 0.0001) than their counterparts. Children exposed to four or more ACEs had lower odds of receiving preventive dental visits than children exposed to less than four ACEs (aOR 0.67; 95 percent CI 0.50–0.89). Children with four or more ACEs had higher odds of decayed teeth than children exposed to fewer than four ACEs (aOR 2.08; 95 percent CI 1.61–2.70), even after controlling for preventive dental care. Conclusions: Pediatricians, dental hygienists, and dentists need to be aware of how childhood trauma may hinder both caregivers and children from engaging in preventive oral health care or dental treatment. The information provided in our study can inform policies and programs that support children's oral health, through the identification and mitigation of childhood trauma.